Dynamic Perviousness of Thrombi in Acute Ischemic Stroke Predicts Clinical Outcome after Reperfusion Therapy - Gergely Bertalan; Miklos Krepuska; Daniel Toth; Jawid Madjidyar; Patrick Thurner; Tilman Schubert; Zsolt Kulcsar (Sci)
Background: Acute ischemic stroke (AIS) is one of the leading causes of death in the industrialized world and causes a heavy personal and economic burden. Thrombus perviousness, measured with pre-interventional computed tomography (CT), is a relatively new imaging biomarker with the potential to estimate clinical outcome in AIS and optimize therapy. However, reported findings on the relationship between thrombus perviousness and clinical parameters in AIS are conflicting. In this study, we investigated the characteristics of the time-resolved contrast agent uptake in thrombi and the predictive potential for clinical outcomes. Methods: We analyzed 55 AIS patients who underwent pre-interventional CT perfusion and recanalization with mechanical thrombectomy. A thrombus with a visible hyperdense artery sign was segmented in 2D. Thrombus standard perviousness was measured as the mean thrombus attenuation increase (TAI) between CT angiography (CTA) and NCCT. For dynamic perviousness, the time-resolved contrast agent uptake curve (CAU) was derived from a 30-phase CT perfusion (CTP) measurement. The rise time (trise) and the TAI increase rate per second (∆d), as well as the time window for the 10th (tW10), 20th (tW20), and 30th (tW30) percentiles of the CAU peak, were calculated. The standard and dynamic perviousness (trise, ∆d, tW10, tW20, and tW30) were analyzed for their associations with clinical outcomes (3-month mRS) with the Wilcoxon signed rank test. Results: Dynamic perviousness was associated with the clinical outcome. The group mean trise and ∆d for thrombi with good clinical outcomes (mRS ≤ 2) were approximately 20% lower (p = 0.04) and 36% higher (p = 0.02) than those for thrombi with poor outcomes (mRS > 2). The time windows for the 10, 20, and 30% maximum contrast agent concentrations in the thrombus were approximately 40% (p = 0.004), 18% (p = 0.02) and 33% (p = 0.004) lower in thrombi with good outcomes than in thrombi with poor outcomes, respectively. Standard perviousness showed no association with clinical outcome. Conclusion: Dynamic perviousness from perfusion imaging retrieves the CAU characteristics of thrombi with greater resolution detail than standard perviousness. Thrombi with relatively fast contrast agent uptake dynamics are more prone to good clinical outcomes than thrombi with slow uptake dynamics.